Pengaruh Faktor Organisasi terhadap Sistem Informasi Sumber Daya Manusia serta Motivasi Karyawan (Studi pada Perusahaan Daerah Air Minum Kota Malang) - Yogatama, Ahmad Nizar; Thoyib, Armanu; Troena, Eka Afnan (Universitas Brawijaya, Indonesia, 2015)
This study aims to know and analyze the organizational factors in which affecting Human Resources Information System adoption, then analyze Human Resource Information System adoptionin which affecting the employee motivation in the Regional Water Company Malang. This study is using quantitative method. Population consists of 36 people. Sample is used census technique. Analysis data is used analysis and Partial Least Square. The results show that organizational factors affected Human Resource Information Systems adoption, organizational factors affected motivation, and only Human Resource Information System adoption affected motivation. In general, e-HRM (Electronic Human Resource Management) and HRIS (Human Resource Information System) can be judged from the context of the organization (training and skills of human resources), however only HRIS adoption can affect employee motivation.